If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(6x) + 19 = 310 Remove parenthesis around (6x) 2 * 6x + 19 = 310 Multiply 2 * 6 12x + 19 = 310 Reorder the terms: 19 + 12x = 310 Solving 19 + 12x = 310 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-19' to each side of the equation. 19 + -19 + 12x = 310 + -19 Combine like terms: 19 + -19 = 0 0 + 12x = 310 + -19 12x = 310 + -19 Combine like terms: 310 + -19 = 291 12x = 291 Divide each side by '12'. x = 24.25 Simplifying x = 24.25
| 0.1x+.7=3.7 | | 9b-1=107 | | 58-10+2x=58 | | 7(a-7)+36=2(a-4) | | 11y-4=5y+4 | | .1x+.07=3.7 | | 3cos((pi)(x))= | | 11y-4=5y | | 7x+12=3(x+6) | | 8b-20=4 | | 10000.00*0.072= | | 3cos(pix)= | | x+2x-=10 | | 2x+9-4(x+1)=3x+9 | | 9x-2=7x+38 | | 0.3(p+6)-0.8(p+6)=-5 | | 3cos(pi)x= | | 16x(x-2)=(8x-25) | | 0.4x-5=.75x-4 | | 0=6x^4-x^3-7x^2+9x+2 | | 16x-9x=840 | | 10t+5(1.4-t)=8 | | -4x+29= | | 7a+7=14 | | 11x+8x=1862 | | 5x(4x+1)(3x-7)=0 | | 2x+9-4x-4(x+1)=3x+9 | | 12(x+2)=24 | | 5x+2=26-3x | | 4(x-1)=x+6 | | v-(-9)=15 | | m+0.72=1.54 |